Protection of Civilians in War: The Role of International Humanitarian Law - Khan, Gawhar Ahmad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
International Humanitarian Law (IHL) is a compilation of laws aimed at limiting the consequences of armed conflict for humanitarian purposes. It safeguards those that are not or are no longer involved in fighting and limits the arms and tactics of warfare. It also protects people’s lives, welfare, and dignity, prohibits torture and inhuman treatment, prescribes fundamental protections for those facing criminal charges, prohibits prejudices, establishes guidelines for women's and children's safety, and regulates facets of the right to food and health. This study, essentially, theoretical and academic, would focus onto bring about the role and importance of International Humanitarian Law in protection and establishing the rights of civilians during the strife and hostilities.